CORRUPTION AND CONFLICT IN MUSLIM-MAJORITY COUNTRIES: A Cross-National Empirical Analysis - Rohmatika, Fiya Ainur; Surwandono, Surwandono (UIN Sumatera Utara, 2025)
Corruption and socio-political conflict remain major challenges in many Muslim-majority societies. This study examines the relationship between corruption and conflict intensity through a cross-national empirical analysis of 20 Muslim-majority countries. Using data from the 2024 Corruption Perceptions Index (CPI) and the Global Peace Index (GPI), Pearson's correlation analysis identifies a strong negative association (r = −0.769), indicating that higher perceived corruption is closely linked to greater conflict intensity. The findings suggest that corruption undermines institutional legitimacy, weakens governance capacity, and intensifies structural vulnerabilities that fuel instability. Despite Islamic normative frameworks emphasizing justice and accountability, persistent corruption reflects a significant gap between ethical ideals and institutional practice across diverse contexts. This study conceptualizes corruption not merely as an administrative failure but as a central driver of conflict dynamics. Addressing the corruption-conflict nexus requires integrated strategies that combine institutional reform, strengthened governance accountability, and context-sensitive ethical approaches to enhance political stability in contemporary Muslim societies.Keywords: Corruption, Conflict, Muslim-Majority Societies, Governance, Political Stability